2022
DOI: 10.1111/psyp.14120
|View full text |Cite
|
Sign up to set email alerts
|

Motivated for movement: Beta activation over the motor cortex resulting from intrinsic and extrinsic motivators

Abstract: Past work on motivation has primarily studied dichotomous distinctions of motivation (e.g., extrinsic or intrinsic). However, focusing on the overall motivational intensity may be better at accentuating the unique differences within and between varying motivators as it pertains to the impetus to act. Specifically, motivational intensity influences neural patterns of beta band frequency (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) as measured by electroencephalography (EEG) that enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 130 publications
1
3
0
Order By: Relevance
“…Also, a beta power decrease on error relative to correct trials was observed across the whole sample. Considering previous work showing that beta band activity is associated with motor processing during a flanker task (Li et al, 2021; Wilhelm et al, 2022), this pattern is consistent with the possibility that beta activity may be related to motor preparation for subsequent trials. Indeed, individuals with greater error‐related beta also had longer RTs on trials that followed the commission of an error (i.e., post‐error trials).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Also, a beta power decrease on error relative to correct trials was observed across the whole sample. Considering previous work showing that beta band activity is associated with motor processing during a flanker task (Li et al, 2021; Wilhelm et al, 2022), this pattern is consistent with the possibility that beta activity may be related to motor preparation for subsequent trials. Indeed, individuals with greater error‐related beta also had longer RTs on trials that followed the commission of an error (i.e., post‐error trials).…”
Section: Discussionsupporting
confidence: 89%
“…Unique to the current study, the OCD group was characterized by reduced beta power decrease (i.e., greater power) on error (but not correct) trials, relative to the control group. Based on previous literature (e.g., Li et al, 2021;Wilhelm et al, 2022), this finding could indicate that participants with OCD are characterized by reduced motor preparation following errors (e.g., greater motor inhibition). Consistent with this possibility, enhanced error-related beta was associated with slower post-error RTs, linking increased beta power on error trials to increased behavioral inhibition on subsequent trials.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Positive Affects that occur after a goal has been achieved, tend to be low in approach-motivational intensity. In a recent study, reserachers [15,16] directly tested whether high (pregoal) versus low (postgoal) approachmotivated PA states would differ in beta suppression and relate to cognitive processes that facilitate goal pursuit. Results revealed that beta suppression was highest in pregoal positive states, relative to postgoal positive and neutral states.…”
Section: Beta Activity Over the Motor Cortex: Measuring Approach-moti...mentioning
confidence: 99%